Clinical profile of Thrombocytopenia in Acute Febrile Illnesses; a hospital-based study - Dhunputh, P.; Acharya, R.; Umakanth, S.; Shetty, S. M.; Mohammed, A. P.; Saraswat, P. P. (Kathmandu University Medical Journal, 2021)
Background Thrombocytopenia is a common haematological abnormality noted in clinical practice, however, it can be missed in cases where specific investigations are not asked for. Acute Febrile Illness with thrombocytopenia is a diagnostic and therapeutic challenge, as thrombocytopenia has an inverse relation to mortality and morbidity in various febrile illnesses. Vector-borne and zoonotic diseases (like malaria, dengue, scrub typhus, and leptospirosis), infections and sepsis are some of the common causes of fever with thrombocytopenia. Objective To identify the causes of fever with thrombocytopenia, assess the clinical complications associated with febrile thrombocytopenia, and overall study the clinical profile of thrombocytopenia in a tertiary care hospital. Method Medical records of all adult patients, admitted to a tertiary level hospital, with fever and thrombocytopenia (platelet count < 1,00,000 /mm3) were assessed (from October 2009 to March 2011). Detailed case history, general physical examination findings, routine and specific examinations were recorded according to a pre-decided format. Data were analysed using SPSS 16.0 Result Acute febrile illness with thrombocytopenia was most commonly seen in Dengue patients. Headache and arthralgia were more commonly encountered in scrub typhus. Platelet transfusions were necessitated in a large number of patients, especially in scrub typhus. Malaria patients had the highest mortality rate. Conclusion Acute Febrile Illnesses (AFI) are of varied origins, and proper diagnosis is imperative. The degree of thrombocytopenia in infections has a prognostic value. It can also help in differential diagnosis and clear identification of aetiology of acute febrile illnesses. Timely identification and management of thrombocytopenia in acute febrile illness can positively impact the overall patient outcome.